2021
DOI: 10.1080/07853890.2021.1970219
|View full text |Cite
|
Sign up to set email alerts
|

Using 360-degree video for teaching emergency medicine during and beyond the COVID-19 pandemic

Abstract: Objective During the COVID-19 pandemic, emergency medicine (EM) teachers had to employ innovative methods to ensure the continuity of the education process. The purpose of this study was to explore the adequacy of the 360-degree video (video 360) technology in EM education in the context of: (a) students' attitudes towards the video 360; (b) students' academic performance in their required examination at the end of the EM course compared to the assessment results of students from the previous acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Nevertheless, students seemed willing to overcome the difficulties and seized every opportunity to improve their preparedness for their chosen career, i.e., the medical profession, in line with other reports about technology-enhanced teaching being well-received by medical students [ 33 ]. Notably, compared with the results reported by Baashar et al [ 33 ], the students who participated in our project obtained good marks in further objective EM examinations at the end of that semester, thus confirming their good preparedness, in addition to their commitment and declared motivation [ 34 ].…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, students seemed willing to overcome the difficulties and seized every opportunity to improve their preparedness for their chosen career, i.e., the medical profession, in line with other reports about technology-enhanced teaching being well-received by medical students [ 33 ]. Notably, compared with the results reported by Baashar et al [ 33 ], the students who participated in our project obtained good marks in further objective EM examinations at the end of that semester, thus confirming their good preparedness, in addition to their commitment and declared motivation [ 34 ].…”
Section: Discussionsupporting
confidence: 76%
“…Six studies revealed that VR represented a helpful learning and training tool during the COVID-19 pandemic in several areas. First, watching 360° videos on desktop displays effectively taught emergency medicine during the COVID-19 crisis [ 102 ]. Second, immersive VR showed relatively better outcomes regarding skills acquired, learning speed, and information retention rates than classroom training in a sample of frontline health workers [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…The second main result of this systematic review is that during the COVID-19 pandemic, VR was a helpful learning tool for medical education and training in several areas, including emergency medicine, nursing, pediatrics, radiology, and cardiology (eg, [100][101][102]). This technology has been successfully used for teaching various topics, including neuroanatomy and clinical anatomy (eg, [84,93]).…”
Section: Principal Findingsmentioning
confidence: 99%
“…Consequently, the number of 360° 3D VR videos has been continuously increasing since the onset of the COVID-19 pandemic. [17][18][19][20]22,35 One of the major add-ons of 360° 3D VR videos is immersion, in this case the feeling of being in the OR. Immersion is crucial for VR applications in general.…”
Section: Surgical Trainingmentioning
confidence: 99%
“…If the microscope video is also embedded in the 360° video, the trainee can not only watch the microsurgical video, but also observe the surgeon's actions and interaction within the OR. Different surgical or procedural 360° videos have already been tested in various medical disciplines and setups [17][18][19][20][21] such as physical examination, 22 laparoscopic surgery 16,23 or gastrointestinal endoscopy. 24 With regard to surgical training, Yoganathan et al, for example, showed in a randomized controlled trial in 2018 that the acquisition of knot-tying skills in surgery residents was better with a 360° 3D VR video than with a 2D video.…”
mentioning
confidence: 99%